Characterization of pilE antisense RNA in Neisseria meningitidis - Tan, F (2016)
Expression of Type four pili is important for colonization and virulence in Neisseria meningitidis, which is a major causative agent of bacterial meningitis and septicaemia. Pili mediate adhesion, twitching motility, DNA uptake, and can be subject to phase and antigenic variation (Av). Pilin expression and Av may be modulated in response to environmental cues; however, the mechanisms of regulation are still unclear. This work demonstrates the identification of a novel cis-encoded RNA on the antisense (AS) strand of pilE, which encodes the major pilin subunit. The AS promoter is conserved in different N. meningitidis isolates, suggesting that the AS RNA may play an important role N. meningitidis biology. By Northern blot and strand-specific qRT-PCR, the AS transcript was shown to be expressed during specific conditions, namely after overnight growth and in response to salt stress. The AS RNA was found to encompass sequences antisense to the entire pilE coding sequence and 5' untranslated region, and extends to a promoter upstream of pilE that drives expression of a G4 small RNA that is important for pilin Av. Noncoding RNAs are increasingly recognized as important regulators of gene expression in bacteria. AS RNAs often modulate expression of the sense mRNA, however in this study, overexpression or deletion of the AS RNA had no significant effect on pilE transcript or pilin levels despite its long stretch of complementarity to the pilE mRNA. Potential trans targets were also investigated by performing RNAseq analysis to identify differentially expressed genes in the absence of the AS RNA. Expression of the AS RNA was found to reduce the frequency of pilE variation. The possible influence of the AS RNA on G4 small RNA transcription was investigated by examining its effect on the levels of G4 small RNA and RNA:DNA hybrids. Although technical issues prevented us from obtaining definitive results, our findings suggest the AS RNA forms RNA:DNA hybrids, adding an additional layer of complexity of molecular processes in the pilE locus of N. meningitidis.